The Effect of Temperature and Amount of Nickel Catalyst on Yield and Bio-Oil Composition in Pyrolysis of Sugarcane Bagasse - Zulia Arifah; Martomo Setyawan; Aditya Waskitha Nugraha; Ahyar Rosidi; Siti Jamilatun (Universitas Darussalam Gontor, 2023)
The abundance of bagasse waste from sugar cane processing needs special attention apart from being used for direct combustion in boilers. Sugarcane bagasse waste can be further processed by pyrolysis so that it will produce bio-oil, bio-gas and char products which have the potential to be used as fuel or high-value chemicals. Pyrolysis of bagasse was carried out to study the effect of temperature and the ratio of the amount of Ni catalyst on the yield and composition of bio-oil in the form of oxygen to carbon (O/C) ratio, hydrogen to carbon (H/C) ratio, higher heating value (HHV), content of oxygenated compounds and range of aromatic compounds. Pyrolysis of bagasse is carried out in a fixed bed reactor with a heating rate of 10-12 ÂºC/minute to the desired temperature. Pyrolysis with and without a catalyst was carried out at a temperature range of 300-600 ÂºC with a variation of Ni catalyst weighing 2.5 grams and 5 grams. Liquid product analysis was tested using GCMS (Gas Chromatography and Mass Spectroscopy) to determine the compound content in the liquid product resulting from pyrolysis of sugarcane bagasse. Bio-oil resulting from pyrolysis of sugarcane bagasse contains several dominant compounds including alcohol, fatty acids, esters, carotenoids and levoglucosan. However, the yield of sugarcane bagasse bio-oil without catalyst was dominated by high levoglucosan, namely 70.52%. Meanwhile, the bio oil resulting from pyrolysis which varied with 2.5 grams and 5 grams of Ni catalyst was dominated by esters, namely 69.07% and 81.68% respectively. These compounds have different chemical properties and applications, and understanding the composition of bio-oil can help in deciding how to use it efficiently.